2020
DOI: 10.15366/reice2020.18.2.006
|View full text |Cite
|
Sign up to set email alerts
|

Competencias del Profesorado de la Escuela Rural Catalana para Abordar la Dimensión Territorial en el Aula Multigrado

Abstract: En este artículo se presentan los resultados parciales de un estudio descriptivo realizado en el marco del proyecto FOPROMAR (2017-1-ES01-KA201-038217). En concreto, se muestran los resultados obtenidos tras la administración del Cuestionario de Competencias del Profesorado de la Escuela Rural (CC-PER) a los maestros y maestras que ejercen su labor docente en las escuelas rurales de Cataluña (n = 276). Además de los datos de contexto, este cuestionario se compone de 30 competencias agrupadas en los siguientes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 4 publications
4
6
0
11
Order By: Relevance
“…The results of this research coincide with those of other studies which show the lack of explicit content on multigrade schools and their teaching in Spanish university programmes (Abós, 2011;Boix and Buscà, 2020;Magro, 2019). No studies on the subject can be found in Slovenia; however, results of Slovenian students' perceptions of Within the framework of Le Cornu's (2009) research, that states that the learning experiences that student teachers have during their training positively, or negatively, affect the expectations of motivation in the future performance of their profession, these results show that the lack of knowledge and understanding of institutional elements, contextual and organisational aspects of educational policies, management of professional relations and elements of pedagogy and multigrade teaching influence their confidence as future teachers in multigrade schools, as well as the level of acquisition of the competencies they express (See Tables 5 and 8).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of this research coincide with those of other studies which show the lack of explicit content on multigrade schools and their teaching in Spanish university programmes (Abós, 2011;Boix and Buscà, 2020;Magro, 2019). No studies on the subject can be found in Slovenia; however, results of Slovenian students' perceptions of Within the framework of Le Cornu's (2009) research, that states that the learning experiences that student teachers have during their training positively, or negatively, affect the expectations of motivation in the future performance of their profession, these results show that the lack of knowledge and understanding of institutional elements, contextual and organisational aspects of educational policies, management of professional relations and elements of pedagogy and multigrade teaching influence their confidence as future teachers in multigrade schools, as well as the level of acquisition of the competencies they express (See Tables 5 and 8).…”
Section: Discussionsupporting
confidence: 90%
“…In general, Slovenian students considered that they had a higher level of acquisition of competences for multigrade teaching compared to Spanish students. From the brief curricular analysis presented, it is found that in both programmes there is no specific subject that declares from the formal curriculum the integration of pedagogy and didactics of the multigrade school, confirming again the statements of Abós (2011), Boix and Buscà (2020); Magro (2019); European Commission (2019) who insist that in the university centres the lack of attention to the concept of teaching in mixed classrooms persists.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Las entrevistas y los códigos construidos sobre el desarrollo de conocimientos y logro de objetivos concuerda con muchas investigaciones, no así con los códigos sobre las dificultades económicas que afectan de manera directa la competencia docente, las cuales se vieron afectadas por familias numerosas y condiciones económicas limitadas, además el código de adquisición de habilidades se mostró limitado por parte del profesorado, debido a falta de capacitación, un currículo general que provoca una falta de dominio del saber ( figura 4), como lo menciona Boix & Buscà (2020), en la cual los Docentes no tienen ninguna adquisición de competencias específicas para desempeñarse en territorios rurales, pues sus títulos provienen como en la presente investigación de las carreras que ofertan las Universidades del país, de la misma manera Núñez-Rojas & Díaz-Castillo (2017), detalla que el porcentaje elevado de Docentes no presentan estudios de posgrado ni Doctorado y solo mantienen el título profesional de pregrado, lo cual se ve afectado por la falta de recursos de Docentes como del Sistema Educativo Nacional, se agrega el cambio por parte del Ministerio de Educación de un currículo general tanto urbano como rural a un currículo priorizado, en el cual varias temáticas se eliminaron en todas las áreas de estudio, consecuentemente produjo falta de transversalidad y diversidad cultural al proceso de enseñanza aprendizaje tal como lo expresa Castro Miranda (2018), en su investigación dice que al existir poca visión integradora, dificulta las competencias en el desarrollo formativo estudiantil y peor aún en la diversidad de la escuela rural, en la investigación el Personal Docente se compone de un mayor número de mujeres, mayores de 30 años de edad y con experiencia en la docencia en el sector privado mayor a dos años, lo que concuerda con la investigación realizada por Minor-Jiménez & Cortés-Dueñas (2019) donde se observa que el sexo femenino se empodera de la enseñanza básica como del bachillerato.…”
Section: Competencias Educativasunclassified